Population genomic analysis uncovers environmental stress-driven selection and adaptation of Lentinula edodes population in China - Xiao, Yang (Sci Rep, 2016)
The elucidation of genome-wide variations could help reveal aspects of divergence, domestication, and adaptation of edible mushrooms. Here, we resequenced the whole genomes of 39 wild and 21 cultivated strains of Chinese Lentinula edodes, the shiitake mushroom. We identified three distinct genetic groups in the Chinese L. edodes population with robust differentiation. Results of phylogenetic and population structure analyses suggest that the cultivated strains and most of the wild trains of L. edodes in China possess different gene pools and two outlier strains show signatures of hybridization between groups. Eighty-four candidate genes contributing to population divergence were detected in outlier analysis, 18 of which are involved in response to environmental stresses. Gene enrichment analysis of group-specific single nucleotide polymorphisms showed that the cultivated strains were genetically diversified in biological processes related to stress response. As the formation of fruiting bodies is a stress-response process, we postulate that environment factors, such as temperature, drove the population divergence of L. edodes in China by natural or artificial selection. We also found phenotypic variations between groups and identified some wild strains that have potential to diversify the genetic pool for improving agricultural traits of L. edodes cultivars in China.